FORMATION OF KNOWLEDGE, SKILLS AND ABILITIES OF FUTURE ENGINEERS IN THE EDUCATIONAL INFORMATION ENVIRONMENT OF THE TECHNICAL UNIVERSITY - Рахманов, В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The article defines and analyzes the components of the formation of knowledge, skills and abilities in of future engineers in the educational information environment of the technical university. The identified components will provide an opportunity to increase the efficiency of the learning process, to deepen the professional knowledge of students and the competence of teachers. Creation of a system of informational, programmed and didactic provision of the institution of higher technical education, the adaptation of software and computerized systems to the conditions of the educational process, justification of the methodology for their use is an actual theoretical and methodological problem, the solution of which will have an important scientific and pedagogical value. Organization of productive interaction of the tutor and students, using the properties of educational and information environment, contributes to the effectiveness of the educational process in the high educational institution, creating conditions for self-realization, self-determination of the student's personality, the creative potential of the individual, the formation of value orientations and moral qualities and their subsequent updating in the profession.